Virtual MoA signing ceremony between UiTM Kelantan Branch & University Al Azhar Indonesia - UiTM Cawangan Kelantan, Unit Komunikasi Korporat (2023)
MACHANG, 09 February - UiTM Kelantan Branch (UiTMCK) and University Al Azhar Indonesia (UAi) have agreed to sign the international strategic partnership by signing the MoA on Academic Visit and Student Academic Visit between the two universities on 30th of January 2023. The ceremony was held online via Zoom Meeting and the UiTMCK Official YouTube channel. UiTMCK and UAi started the Memorandum of Understanding in 2019 and will continue to collaborate in pursuing excellence in the fields of academics. The ceremony was chaired by Prof. Dr Haji Abdol Samad Nawi, the Rector of UiTMCK, and participated by the top management of UiTMCK. UAi was represented by Prof. Dr Ir. Asep Saefuddin, the Rector of University Al Azhar Indonesia. Prof. Dr Haji Abdol Samad Nawi stated the collaborative activities that are conducted are to ensure academic knowledge growth and to enhance research ability. Our collaborative activities include Public Speaking Competition, Collaborative Teaching, International Information Management Online Showcase, and Art & Design Fashion Show. Furthermore, UiTM has signed over 707 MoU/ MoA with universities worldwide and has conducted more than 500 international programs and activities with our international partners physically and virtually.